Morinda citrifolia edible leaf extract enhanced immune response against lung cancer - Lim, Swee Ling; Goh, Yong Meng; Mohamed Mustapha, Noordin; Rahman, Heshu Sulaiman; Othman, Hemn Hassan; Abu Bakar, Nurul Ain; Mohamed, Suhaila (Royal Society of Chemistry, 2016)
Lung cancer causes 1.4 million deaths annually. In the search for functional foods as complementary therapies against lung cancer, the immuno-stimulatory properties of the vegetable Morinda citrifolia leaves were investigated and compared with the anti-cancer drug erlotinib. Lung tumour-induced BALB/c mice were fed with 150 mg kg−1 or 300 mg kg−1 body weight of the leaf extract, or erlotinib (50 mg kg−1 body-weight) for 21 days. The 300 mg kg−1 body weight extract significantly (and dose-dependently) suppressed lung tumour growth; the extract worked more effectively than the 50 mg kg−1 body weight erlotinib treatment. The extract significantly increased blood lymphocyte counts, and spleen tissue B cells, T cells and natural killer cells, and reduced the epidermal growth factor receptor (EGFR) which is a lung adenocarcinoma biomarker. The extract also suppressed the cyclooxygenase 2 (COX2) inflammatory markers, and enhanced the tumour suppressor gene (phosphatase and tensin homolog, PTEN). It inhibited tumour growth cellular gene (transformed mouse 3T3 cell double minute 2 (MDM2), V-raf-leukemia viral oncogene 1 (RAF1), and mechanistic target of rapamycin (MTOR)) mRNA expression in the tumours. The extract is rich in scopoletin and epicatechin, which are the main phenolic compounds. The 300 mg kg−1Morinda citrifolia leaf 50% ethanolic extract showed promising potential as a complementary therapeutic dietary supplement which was more effective than the 50 mg kg−1 erlotinib in suppressing lung adenocarcinoma. Part of the mechanisms involved enhancing immune responses, suppressing proliferation and interfering with various tumour growth signalling pathways.